The Effect of Word Wall Media on The Class Counting Operation Skills - Sitepu, Silvi Anggraeni Br; Pulungan, Lilik Hidayat (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research aimed to investigate the effect of word wall learning media on students' multiplication calculation skills. A quantitative research approach was employed using a Pre-Experimental Design, specifically a One-Group Pretest-Posttest Design. The instrument's validity and reliability were tested using the Statistical Package for the Social Sciences (SPSS) software. The analysis technique used was the t-test, with the null hypothesis (H0) being rejected and the alternative hypothesis (Ha) being accepted. The t-test results showed a calculated t-value of 21.570, while the critical tvalue (ttable) had a significance level of 0.000 and 27 degrees of freedom was 2.051. At a 5% significance level (21.570 > 2.051) and a p-value of less than 0.05 (p=0.000 < 0.05), it was concluded that Ha was accepted and H0 was rejected. This indicates a significant difference between pre-test and post-test scores, demonstrating that the word wall media positively influences the multiplication calculation skills of fifth-grade students at UPT SPF SDN 105308 Namo Bintang.